2007
DOI: 10.1038/sj.onc.1210893
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 inhibition has opposing effects on wild-type and mutant p53 and induces p21 expression and cytotoxicity irrespective of p53/ATM status in chronic lymphocytic leukaemia cells

Abstract: In chronic lymphocytic leukaemia (CLL), mutation/ deletion of TP53 is strongly associated with early disease progression, resistance to chemotherapy and short patient survival. Consequently, there is a pressing need to develop novel treatment protocols for this high-risk patient group. The present study was performed to evaluate Hsp90 inhibition as a possible therapeutic approach for such patients. Primary CLL cells of defined ataxia telangiectasia mutated (ATM)/p53 status were incubated with the Hsp90 inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 73 publications
7
61
0
1
Order By: Relevance
“…Previous studies have also shown that mutant p53 protein bound to HSP90 does not function as a tumour suppressor, and that the HSP90-mutant p53 complex can interfere with the functions of normal p53 by inducing formation of heterodimers, between normal and mutant p53, and inappropriate transactivation of p53-regulated target genes (Lin et al, 2008). Impairment of wildtype p53 functions, as a result of interference induced by the HSP90-mutant p53 complex, may help facilitate the upregulation of pro-proliferation and survival genes, normally controlled by this protein (De Maio, 2011;Whitesell et al, 2003).…”
Section: The Heat Shock Responsementioning
confidence: 99%
“…Previous studies have also shown that mutant p53 protein bound to HSP90 does not function as a tumour suppressor, and that the HSP90-mutant p53 complex can interfere with the functions of normal p53 by inducing formation of heterodimers, between normal and mutant p53, and inappropriate transactivation of p53-regulated target genes (Lin et al, 2008). Impairment of wildtype p53 functions, as a result of interference induced by the HSP90-mutant p53 complex, may help facilitate the upregulation of pro-proliferation and survival genes, normally controlled by this protein (De Maio, 2011;Whitesell et al, 2003).…”
Section: The Heat Shock Responsementioning
confidence: 99%
“…Clinical trial evidence to date indicates that patients with genetic abnormalities impacting on the p53 pathway need treatment with agents that can act independently of this pathway. It is therefore relevant that the apoptosis-inducing actions of the NF-kB inhibitor parthenolide, 65 roscovitine, 66 flavopiridol, 67 the heat-shock protein 70 inhibitor 2-phenylacetylenesulfonamide 68 and the heat-shock protein 90 inhibitor geldanamycin 69 on CLL cells are independent of p53 status. LC-1, a parthenolide derivative with improved pharmacodynamic properties, is currently in clinical trials (C Pepper, University of Cardiff, personal communication).…”
Section: Therapeutic Strategies For Cll Patients With a Dysfunctionalmentioning
confidence: 99%
“…Blocking of HSP90 was shown to result in reduced invasiveness in vitro and in decreased tumor cell proliferation, vascularization as well as an improved efficacy of conventional therapy strategies in vivo (Moser et al 2007). Further, HSP90 expressed by cancer cells protects against apoptosis (Rashmi et al 2003), down-regulates tumorsuppressing signals such as TP53 (Lin et al 2008) and enables replicative immortality through enhanced telomerase assembly (Akalin et al 2001). HSP90 function is thereby implicated in the establishment of each of the hallmarks of cancer (Neckers 2007) that were first proposed and recently extended by Hanahan and Weinberg (2011).…”
Section: Introductionmentioning
confidence: 99%